Evaluation of tropical legumes as plants for the ensilage - Tosi, Hugo; Faria, Vidal Pedroso de; Silveira, Antônio Carlos; Pereira, Ricardo Luz (Pesquisa Agropecuaria Brasileira, 2014)
A research trial was carried out at São Manuel, SP, Brazil, in order to identify the problems associated with the ensilage of tropical legumes. The species studied were: Centrosema pubescens, Galactia striata, Phaseolus atropurpureus (cv. Siratro) and Glycine wightii. Samples were taken at 56, 90 and 124 days of vegetative growth for the analysis of dry matter, soluble carbohydrate and buffering capacity to hydrochloric acid. The dry matter content of Phaseolus atropurpureus was considered to be very low, where as the other species presented over 30% dry matter only when the plants had 124 days of vegetative growth. All the species showed a very low soluble carbohydrate content and so, it was proposed that it would be necessary to include an additive for estimulation of the lactic fermentation. The buffering capacity was very high for the species studied and this fact could be aserious problem for the ensilage.